The Relationship Between Communication Practice and Organizational Performances in Organizations from Europe - Leković, Božidar; Berber, Nemanja (Industrija, 2014)
The basic goal of the research in this paper was to explore the differences between private organizations in Europe regarding their organizational performances in context of the existence and development of communication practices. The subject of the research was the analysis of communication practice and organizational performances in private-owned organizations in 25 European countries. Methodology of the research included the exploration of the sample from the CRANET, an international HRM project in the period 2008/2010. Authors used statistical techniques to prove stated hypotheses: descriptive statistics, chi square and t-test. Findings of the research pointed to the statistically significant differences between private companies that inform their employees about business strategy, financial results and organization of work regarding organizational performances. Also, there were presented trends of the usage of different communication techniques in countries of Europe. Private-owned firms in Europe usually perform direct “up” communication and verbal communication in the process of communication between managers and employees. Regarding the internalization of the business, authors found that companies that operate mainly on international market usually inform their employees about strategy, finances and organization of work more than companies that operate on local market.